The spoIIE Homolog of Epulopiscium sp. Type B Is Expressed Early in Intracellular Offspring Development - Miller, David A. (American Society for Microbiology, 2011)

(untitled)
Epulopiscium sp. type B is an enormous intestinal symbiont of the surgeonfish Naso tonganus. Intracellular offspring production in Epulopiscium shares features with endospore formation. Here, we characterize the spoIIE homolog in Epulopiscium. The timing of spoIIE gene expression and presence of interacting partners suggest that the activation of σ(F) occurs early in Epulopiscium offspring development.